Surfactant Effects on Microemulsion-Based Nanoparticle Synthesis - Concha Tojo (Materials, 2010)
The effect of the surfactant on the size, polydispersity, type of size distribution and structure of nanoparticles synthesized in microemulsions has been studied by computer simulation. The model simulates the surfactant by means of two parameters: the intermicellar exchange parameter, kex, related to dimer life time, and film flexibility parameter, f, related to interdroplet channel size. One can conclude that an increase in surfactant flexibility leads to bigger and polydisperse nanoparticle sizes. In addition, at high concentrations, the same reaction gives rise to a unimodal distribution using a flexible surfactant, and a bimodal distribution using a rigid one. In relation to bimetallic nanoparticles, if the nanoparticle is composed of two metals with a moderate difference in reduction potentials, increasing the surfactant flexibility modifies the nanoparticle structure, giving rise to a transition from a nanoalloy (using a rigid film) to a core-shell structure (using a flexible one).